2019
DOI: 10.1021/acsami.9b04498
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization-Induced Polarization of Graphene Sheets by Intercalation-Polymerized Polyaniline toward High Performance of Microwave Absorption

Abstract: An intercalation polymerization is applied to regulate the hybridizing structures of polyaniline@graphene (PANI@GE). Polarization of GE sheets is realized, which is attributed to the hybridization by the in situ intercalation-polymerized PANI molecules. The polarizing effect on GE is confirmed by characterizations and density functional theory calculations, and the results indicate that distinct p−π and π–π interactions exist between the PANI molecules and the GE sheets. As a result, this new structural hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 41 publications
2
37
0
Order By: Relevance
“…However, it can be obviously observed that the peak of HGAS and BGAS at G band is gradually down-shifted to 1,588 and 1,586 cm −1 respectively after thermal reduction, which can be attributed to the recovery of the hexagonal network of carbon atoms with defects [22]. The D/G intensity ratio increased, which is typically stated to be due to the decrease in the average size of the sp 2 domains that is typically stated as arising from new (or more) graphitic domains being formed and the sp 2 cluster number increasing [4]. Furthermore, The broad 2D peak at 2,710.4 cm −1 indicates the turbostratic structure in the stacking of graphene sheets [6].…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…However, it can be obviously observed that the peak of HGAS and BGAS at G band is gradually down-shifted to 1,588 and 1,586 cm −1 respectively after thermal reduction, which can be attributed to the recovery of the hexagonal network of carbon atoms with defects [22]. The D/G intensity ratio increased, which is typically stated to be due to the decrease in the average size of the sp 2 domains that is typically stated as arising from new (or more) graphitic domains being formed and the sp 2 cluster number increasing [4]. Furthermore, The broad 2D peak at 2,710.4 cm −1 indicates the turbostratic structure in the stacking of graphene sheets [6].…”
Section: Resultsmentioning
confidence: 96%
“…Meanwhile, a new broad peak at around 22.5 o can also be found, this may be attributed to the partial stacking of GO sheets which are incompletely oxidized due to the squeezing effect of the ice crystals [23]. After thermal reduction to HGAS and BGAS, a sharp peak at 25.3 o appears with the disappearance of the HGOAMs diffraction peaks, which attributes to the re-stacking of graphene layers and indicates the efficient deoxygenation of GO sheets and a highly crystalline "graphitic" structure after annealing [4]. Besides, a weak peak locating at 43° is the evidence of the turbostratic structure, which is consistent with the Raman data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complex permittivities of these synthesized hybrids are given in Figure 5(a and b). Both the real and imaginary parts decrease with an increase in frequency, indicating a frequency dispersion behavior induced by the enhanced polarization lagging in the high frequency [46,47]. The dielectric behaviors of McM@rGO majorly originate from the interfaces between nanoparticles and graphene layers as well as the polarization of residual functional groups [48].…”
Section: Considering the Intrinsic Ferromagnetism Of Nife 2 O 4 Fenmentioning
confidence: 99%
“…Nowadays, with the rapid development of electronic information technology, electromagnetic radiation and pollution originating from electronic devices pose a threat to human health and information safety [1][2][3][4][5][6] and consequently the design and fabrication of microwave absorption materials which can dissipate microwave energy efficiently has become an urgent requirement [7][8][9]. In recent years, extensive efforts on the design of microwave absorbers have been focused on strengthening reflection loss (RL), broadening absorption bandwidth and reducing weight as well as thickness.…”
Section: Introductionmentioning
confidence: 99%